2012
DOI: 10.1007/s00383-011-3039-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in children: botulinum toxin is a safe and effective treatment option

Abstract: BoNT-A has a role in a carefully selected subgroup of children with overactive bladder symptoms including those with medication side effects and treatment compliance issues. It may have a role in patients who do not respond to conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
0
21
1
5
Order By: Relevance
“…109 Published data are continuing to demonstrate that detrusor BoNTA injection is a safe and effective treat ment of urinary incontinence episodes in children with nonneurogenic OAB. 110,111 Dysfunctional voiding is highly prevalent in paedi atric patients with NDO or nonneurogenic OAB. 112 Injections of BoNTA at a dose of 50-100 units resulted in normalization of the voiding curve and decreased PVR volume in this patient population.…”
Section: Ndo Owing To Neuropathiesmentioning
confidence: 99%
“…109 Published data are continuing to demonstrate that detrusor BoNTA injection is a safe and effective treat ment of urinary incontinence episodes in children with nonneurogenic OAB. 110,111 Dysfunctional voiding is highly prevalent in paedi atric patients with NDO or nonneurogenic OAB. 112 Injections of BoNTA at a dose of 50-100 units resulted in normalization of the voiding curve and decreased PVR volume in this patient population.…”
Section: Ndo Owing To Neuropathiesmentioning
confidence: 99%
“…El efecto es temporal, de 6 a 9 meses, y se requieren inyecciones repetidas (54). Se ha encontrado respuesta completa en 74,2 % de los hombres y 54,5 % de las mujeres y respuesta parcial en 20 % de los hombres y 18,2 % de las mujeres (55). Los posibles efectos adversos son retención urinaria, cistitis y riesgo de infección del tracto urinario (25).…”
Section: Tratamiento Farmacológico Anticolinérgicosunclassified
“…Several recent publications have reported the use of BTA for idiopathic detrusor overactivity in children refractory to other forms of therapy [41]. McDowell et al presented a series of 57 patients with OAB resistant to standard urotherapy who were treated with BTA and antimuscarinics [42]. These authors observed success in 74.2 % of males and 54.5 % of females and partial success in 20 % of males and 18.2 % of females [42].…”
Section: Day Wettingmentioning
confidence: 99%
“…McDowell et al presented a series of 57 patients with OAB resistant to standard urotherapy who were treated with BTA and antimuscarinics [42]. These authors observed success in 74.2 % of males and 54.5 % of females and partial success in 20 % of males and 18.2 % of females [42]. The effect is unfortunately not permanent, lasting only 6–9 months, and repeated injections are necessary.…”
Section: Day Wettingmentioning
confidence: 99%